Why Regulate Banks? - Henrik Borchgrevink; Ylva Søvik; Bent Vale (Norges Bank, 2013)
In this note we seek to provide a first guide to how the economic literature explains the rationale for regulating banks. The guide is not exhaustive with respect to academic papers covered. Neither do we elaborate on how banks should be regulated; we only mention key measures in existing regulation.
hdl:11250/2506991
Keywords: 330